How children learn to produce appropriate referring expressions in narratives: The role of clarification requests and modeling - Carmiol Barboza, Ana María (2018)
Asking children to clarify themselves promotes their ability to uniquely identify objects in referential communication tasks. However, little is known about whether parents ask preschoolers for clarification during interactions and, if so, how. Study 1 explored how mothers clarify their preschoolers’ ambiguous descriptions of the characters in their narratives, and whether clarification requests affect children's repairs of their ambiguous descriptions. Mothers were found to use different strategies, including signaling misunderstanding and modeling appropriate descriptions. Presence of these different strategies predicted children's ability to provide informative repairs. Study 2 tested the effect of children's experience with signaling misunderstanding and modeling on their ability to uniquely identify the characters of a story on a second narration. Experiencing modeling, but not misunderstandings, positively affected children's provision of appropriate descriptions during second narrations. Findings are discussed in terms of the role of imitation in driving referential development.